Transformative Cyber Security Model for Malaysian Government Agencies - Perumal, Sundresan; Ali Pitchay, Sakinah; Narayana Samy, Ganthan; Shanmugam, Bharanidharan; Magalingam, Pritheega; Hasan Albakri, Sameer (International Journal of Engineering and Technology, 2018)
The growth of cyberspace world has uprising government agencies in a new way to serve citizen in a proactive, efficient and productive manner. To have an open, stable and vibrant cyberspace, governments should be more resilient to cyber-attacks and able to protect all government agencyâ€™s interest in cyberspace. Therefore, the government needs a transformative cyber governance security model to protect valuable government agenciesâ€™ information. The model should be able to detect, defend and deter the vulnerabilities, threats and risks that will emerge in the day to day government administration operation. This paper has introduced a study for some existing cyber governance security models. Thus, it helps in determining the main features of the required model.Â Â